Uneven clustering routing protocol based on dynamic partition for wireless sensor network - Yan-qing SUN; Jian PENG; Tang LIU; Xiao-hai CHEN (Tongxin xuebao)
To solve the “hot spots” problem caused by uneven load energy,a novel distributed clustering routing protocol was proposed.Its core is an uneven clustering routing protocol based on dynamic partition(UCDP).In UCDP,the entire network’s energy consumption is balanced by dynamic partitioning,making the regions closer to the sink node with smaller nodes,which can preserve some energy for inter-region data forwarding.Considering the distance factor and residual energy factor for uneven clustering in each region,cluster-heads and region-heads work together in UCDP.Via the combination of single-hop and multi-hop,DBUP has established an optimal energy-balanced routing protocol.Simulation results show that UCDP has good stability,and significantly prolongs the network life.